Emerging trends and hot spots in autoimmune thyroiditis research from 2000 to 2022: A bibliometric analysis - Li, Qiuxian; Yang, Wanyu; Li, Jiashu; Shan, Zhongyan (Frontiers in Immunology, 2022)
Background Autoimmune thyroiditis (AIT) is the most common autoimmune disease, affecting numerous patients worldwide. Many studies have been published on AIT. However, to date, no article has systematically assessed the related literature. Therefore, we conduct a bibliometric analysis on AIT to reveal the dynamic scientific developments and help researchers gain a global perspective while exploring the hotspots and development trends. Methods AIT-related articles and reviews from 2000 to 2022 were retrieved from the Web of Science Core Collection (WoSCC). Three software programs (VOSviewer, CiteSpace, Pajek) were employed to analyze the contribution and co-occurrence relationships of different countries/regions, institutes, journals, authors and references, and also keywords in this field. Results 2290 articles and reviews were analyzed. Articles regarding AIT stably rose in number every year. During the past 20 years, researchers have focused on IgG4-related thyroiditis, IFN-α treatment, etc. The focus has shifted to oxidative stress in thyroid disease, the relationship between papillary thyroid carcinoma and AIT and the effect of vitamin D supplementation on AIT. These publications mainly come from 120 countries led by China, Italy and the United States. The top 20 institutions contribute 25.20% of all the documents, and 6 of them are from China. The most prolific institution was the University of Pisa. Thyroid was the journal both the most-published and most-cited in the field, and of the co-cited journals, the Journal of Clinical Endocrinology and Metabolism had the highest number of citations. A total of 10941 authors were identified, among which Teng Weiping and Shan Zhongyan had the most publications, and Alessandro Antonelli was co-cited most often. In terms of potential hotspots, keywords with strong bursts up to now were “oxidative” (2018-2022), “vitamin D” (2016-2022), “polymorphism” (2019-2022) and “association” (2020-2022). Conclusion Bibliometric analysis of the outputs of AIT shows an overview of the current status of the research on AIT. The associations between vitamin D, papillary thyroid carcinoma and AIT are major research frontiers. However, further research and collaboration are still required worldwide. Our findings can help researchers grasp the research status of AIT and quickly determine new directions for future research.